Experimental Validation of ADALINE Least Mean Square Algorithm in a Three-Phase Four-Wire DSTATCOM to Enhance Power Quality. Issue 8 (8th May 2020) - Penthia, Trilochan; Panda, Anup Kumar; Mangaraj, Mrutyunjaya
Abstract: The requirement of a robust and adaptive control algorithm in active filters is inevitable nowadays. In this paper, an ADAptive LINEar neuron (ADALINE) based Least Mean Square (LMS) control algorithm is proposed for a three-phase-four-wire (3 P 4 W ) distribution power system under unbalanced loading conditions. The proposed controller has a unique inbuilt characteristic to extract the fundamental active positive sequence component from an unbalanced load current. Particularly, the control algorithm is intended to calculate an adaptive and suitable amplitude for the three-phase reference source currents which are used for the switching pulse generation in the subsequent steps. Moreover, the Distribution STATic COMpensator (DSTATCOM) is performed to eliminate harmonic contents of supply current and harmful excessive neutral current in the system. Further, the DC-link voltage is regulated in order to reduce the power loss across the DSTATCOM, and to attain a balanced, high-quality power availability at the Point of Common Coupling (PCC). The proposed system is accomplished in the MATLAB2014a/Simulink, and a low power rated 3 P 4 W DSTATCOM prototype incorporating with the dSPACE1104 real-time environment to verify the proposed control algorithm.